Children intoxicated by alcohol in Nottingham and Glasgow, 1973-84. Issue 6519 (22nd February 1986) - Beattie, J O; Hull, D; Cockburn, F
Abstract : The circumstances of ingestion, clinical course, and long term sequelae were examined retrospectively in 143 children (108 boys, 35 girls) admitted with acute alcohol intoxication in Glasgow and Nottingham over the 12 years 1973-84. Fifty three of the children were aged less than 7 years and 90 were aged 7-14. Twelve of the children were hypoglycaemic on arrival at hospital. Trauma related to intoxication occurred in 14 cases, and nine boys became drunk under duress, which in four cases was associated with sexual abuse.